2-Cys peroxiredoxin is required in successful blood-feeding, reproduction, and antioxidant response in the hard tick Haemaphysalis longicornis. Issue 1 (December 2016) - Kusakisako, Kodai; Galay, Remil; Umemiya-Shirafuji, Rika; Hernandez, Emmanuel; Maeda, Hiroki; Talactac, Melbourne; Tsuji, Naotoshi; Mochizuki, Masami; Fujisaki, Kozo; Tanaka, Tetsuya
Abstract Background Ticks are obligate hematophagous arthropods that feed on vertebrate blood that contains iron. Ticks also concentrate host blood with iron; this concentration of the blood leads to high levels of iron in ticks. The host-derived iron reacts with oxygen in the tick body and this may generate high levels of reactive oxygen species, including hydrogen peroxide (H2 O2 ). High levels of H2 O2 cause oxidative stress in organisms and therefore, antioxidant responses are necessary to regulate H2 O2 . Here, we focused on peroxiredoxin (Prx), an H2 O2 -scavenging enzyme in the hard tickHaemaphysalis longicornis . Methods The mRNA and protein expression profiles of 2-Cys peroxiredoxin (HlPrx2) inH. longicornis were investigated in whole ticks and internal organs, and developmental stages, using real-time PCR and Western blot analysis during blood-feeding. The localization of HlPrx2 proteins in tick tissues was also observed by immunostaining. Moreover, knockdown experiments ofHlPrx2 were performed using RNA interference to evaluate its function in ticks. Results Real-time PCR showed thatHlPrx2 gene expression in whole ticks and internal organs was significantly upregulated by blood-feeding. However, protein expression, except in the midgut, was constant throughout blood-feeding. Knockdown of theHlPrx2 gene caused significant differences in the engorged body weight, egg weight and hatching rate for larvae as compared to the control group. Finally, detection of H2 O2 after knockdown ofHlPrxs in ticks showed that the concentration of H2 O2 significantly increased before and after blood-feeding. Conclusion Therefore, HlPrx2 can be considered important for successful blood-feeding and reproduction through the regulation of H2 O2 concentrations in ticks before and after blood-feeding. This study contributes to the search for a candidate target for tick control and further understanding of the tick's oxidative stress coping mechanism during blood-feeding.